The mission bell. - Politi, Leo 1908- (New York Scribner, 1953)
Father Serra and the Indian boy who accompanies him on his journeys watch their dream come true as the missions are built in California.
Keywords: Serra, Junipero -- 1713-1784.; California -- History -- Fiction. -- To 1846.